2022
DOI: 10.1038/s41598-022-15206-6
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of a differentiation-related prognostic nomogram based on single-cell RNA sequencing in clear cell renal cell carcinoma

Abstract: Renal cell carcinoma (RCC) is a kidney cancer that is originated from the lined proximal convoluted tubule, and its major histological subtype is clear cell RCC (ccRCC). This study aimed to retrospectively analyze single-cell RNA sequencing (scRNA-seq) data from the Gene Expression Omnibus (GEO) database, to explore the correlation among the evolution of tumor microenvironment (TME), clinical outcomes, and potential immunotherapeutic responses in combination with bulk RNA-seq data from The Cancer Genome Atlas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Various nomograms have been identified to determine the prognosis of ccRCC patients. For instance, Xia et al [ 12 ] constructed a prognostic nomogram based on the prognostic risk signature and clinicopathological characteristics, which exhibited high accuracy and a robust predictive performance. The study by Zhu et al [ 30 ] reported that combining methylation risk scores with conventional clinical covariates improved the prediction of clinical prognosis in ccRCC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various nomograms have been identified to determine the prognosis of ccRCC patients. For instance, Xia et al [ 12 ] constructed a prognostic nomogram based on the prognostic risk signature and clinicopathological characteristics, which exhibited high accuracy and a robust predictive performance. The study by Zhu et al [ 30 ] reported that combining methylation risk scores with conventional clinical covariates improved the prediction of clinical prognosis in ccRCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nomograms are established based on Cox regression analysis results and are widely used for cancer prognosis, primarily because of their ability to reduce statistical predictive models to a single numerical estimate of the probability of an event, such as death or recurrence [ 10 , 11 ]. In ccRCC patients, a nomogram combining differentiation-related gene (DRG)-based risk score and prognostic clinicopathological variables was previously constructed to provide a visual method for determining prognosis [ 12 ]. However, another nomogram based on risk gene signature and clinical features may provide a practical method for recurrence prediction and facilitate personalized management of ccRCC patients after surgery [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the marker genes in previous study, we annotated the two distinct SPP1+ TAM and C1QC + TAM subpopulations, and consistent with previous study, our trajectory analysis showed that an intermediate state of monocyte-like precursors gave rise to TAM subpopulations in tumor mass [ 18 ]. Several previous studies have utilized the DRGs to construct risk signatures for predicting the prognosis of liver cancer, lung cancer, renal cancer and osteosarcoma [ [35] , [36] , [37] , [38] ]. However, no study has extracted the genes expressed along TAM differentiation lineage for the construction of a prognostic signature for CRC.…”
Section: Discussionmentioning
confidence: 99%